1990
DOI: 10.1111/j.1365-2672.1990.tb02543.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and propagation of phages naturally associated with the aizawai variety of Bacillus thuringiensis

Abstract: This study describes the isolation of a phage, using mitomycin C and u.v. light, from each of four strains (HD67, HD130, HD228 and HD248) of Bacillus thuringiensis H-serotype 7 (var. aizawai). It also describes the isolation of two indicator strains (12.13 and HD102) for these phages (phi HD67, phi HD130, phi HD228 and phi HD248) and the ideal conditions, using these indicator strains, for maximum phage production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…Other probably similar phage, φHD248, is described above. Generalized transduction was demonstrated for the φHD248, which confirms that such phages can be useful for limited spectra of hosts (Inal et al 1990(Inal et al , 1992(Inal et al , 1996.…”
Section: Potentially Transducing Phages For the B Cereus Groupsupporting
confidence: 75%
See 1 more Smart Citation
“…Other probably similar phage, φHD248, is described above. Generalized transduction was demonstrated for the φHD248, which confirms that such phages can be useful for limited spectra of hosts (Inal et al 1990(Inal et al , 1992(Inal et al , 1996.…”
Section: Potentially Transducing Phages For the B Cereus Groupsupporting
confidence: 75%
“…The temperate phages φHD67, φHD130, φHD228 and φHD248 isolated after UV-induction from the subspecies aizawai (Inal et al 1990) have been shown to mediate both intra-subspecific ( aizawai) and inter-subspecific ( aizawai-kurstaki) generalized transduction (Inal et al 1992). The phage ϕHD248 was used for genetic analysis of B. thuringiensis subsp.…”
Section: Gene Transduction Experimentsmentioning
confidence: 99%
“…This generates nicks in supercoiled DNA (Gonzalez & Carlton, 1980) but it did not alter the migration of the #HD248 DNA, unlike that of the control ligated 3, DNA, for which a decrease in the amount of circular DNA was observed (Inal, 1988). t Bands A1 and C1 are minor bands present in submolar amounts (see text).…”
Section: Hd248 Dna Lacks Cohesive Endsmentioning
confidence: 99%
“…UV light can induce bacteriophage production in B. thuringiensis subsp. aizawai (14) and in B. thuringiensis subsp. kurstaki HD-1 as measured by lysis of B. cereus 569 (A. Aronson, unpublished results), so a major reason for the extreme sensitivity of these plasmidbearing strains could be phage induction.…”
Section: Resultsmentioning
confidence: 99%